The phenomenon of air pollution And health effects on man - محمود, ميسون طه (Al-Adab Journal, 2019)
The healthy fresh air which is not Tkhalth contaminants (foreign bodies) air and solid, chemical and vital air which is appropriate to human health and comfort.In the current era became fresh air elusive in the world regions to humans and under the direct sovereignty to mix with the air of those areas of exotic materials variety of different sources of quality (natural Kalmsadr, volcanoes, forests and human and laboratories, factories, fires, cars, transport, and resulting in fuel combustion in homes).The most dangerous air pollutants on human health are contaminants of human chemical nature, some of which turn out to be other pollutants secondary the most dangerous of the major and growing dangerous chemical pollutants and increase its focus on its source areas and nearby of the major cities and regions of laboratories and factories and crowded in the population and the situation topographic cities an important role in the severity of the concentration of pollutants as a result of which the most important in the situation is the situation that the pelvic. The air situation plays a big role, too. When calm air and heat increases the concentration of pollutants coup and whenever the weather is more moisture was more dangerous air pollutants on human health.And operates six gases about 99.97% of the volume of air which is (nitrogen, ozone, oxygen, water vapor.Irgun and carbon dioxide), and some of the gases increase very little, but it is of special importance as a gas ozone, which absorbs the bulk of solar ultraviolet radiation either water vapor vary rate from one place to another and range rate between 0.5-4% in the atmosphere of the size and the rate is low in the polar regions and desert about 0.2% and high in the tropical sunshine between 3.4% and most of the water vapor is concentrated in the bottom layer of the atmosphere and be virtually non-existent over 10-15km height .otakhtlv components of the atmosphere and its properties and attributes of public vertically and centered about 99.9% of the mass of air in the lower fifty km, and about 0.997% of the mass between high 50-100km.And the rest of the block specific prevalence in the rest of the atmosphere is also less air Scouts whenever Artfna to the top consists of 1.2 kg / m 3, at sea and 0.7 kg / m 3 at the height of 5 km.I have been given to the issue of air pollution considerable attention by the rest of the world of the importance of the air in the continuity of life, especially if we know that lung every human body receives daily about (15 kg) from the atmosphere while the body absorbs only (2.5 kg) of water and less than (1.5 kg) of food.That air pollution is evidence it contains exotic materials, or materials of the same but at rates greater than the greatest reduction of its presence, and that this increase in the negative influences associated with the geographical environment.It can be air pollution locally for its association with specific areas caused by the cities and major industrial areas, or be universally deployed on the territory of many countries of the world such as pollution caused by radiation or atomic projectiles caused by volcanic